Unbalance Source Voltage and Load Current Mitigation Using UPQC based on Power Impelling Optimization Technique - R. , Rajarajan; R. , Prakash (International Journal of Psychosocial Rehabilitation, 2020)
Power quality is the most important one of the transmission and distribution system. In recent years, various power electronics devices have been implemented, so the load voltage is various, and it causes different problems. The voltage sag, swell, and harmonics are the power quality problems presented in this problem that cause damage in the system load, so the power quality improvement in this system is very important. The Unified Power Quality Control is used to reduce the power supply problems. It can be implemented based on the proposed Power Impelling Optimization Technique (PIOT); it can attain the improvement of power quality in the power transmission system. In this UPQC system contain series and shunt converter to compensate the unbalanced voltage and reduce the problem like sag, swell voltage and harmonics of this system. The proposed system is getting the reference voltage and current value in the transmission line and analyzing the problem of this process and giving the proper switching to the converter via the controller. The active power filter of shunt and series is used to reduce the loss in the transmission line and give quality power to the load. The proposedPower Impelling Optimization Technique(PIOT)is utilized to increase the quality of power and reduce the losses. This proposed system analysis in the Simulink software to get the result of this system, the simulation shows the system input, output voltage, and total harmonic distortion.